Hospital-acquired pneumonia and ventilator-associated pneumonia in adults at Siriraj Hospital: Etiology, clinical outcomes, and impact of antimicrobial resistance - Peerawong Werarak (2018)
Background: Nosocomial pneumonia (NP), hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP), is an important cause of morbidity and mortality in hospitalized patients. One of the factors contributing to a high mortality rate of HAP and VAP could be antibiotic resistance among the causative agents. Objective: To determine prevalence of bacterial pathogens clinical features, risk factors of HAP and VAP, antimicrobial resistance among major respiratory pathogens, clinical implication of antimicrobial resistance, antimicrobial regimens used, and treatment outcomes of adult patients with HAP and VAP at Siriraj Hospital. Material and Method: This was a prospective, hospital-based, active surveillance study on HAP and VAP in hospitalized adults at Siriraj Hospital from December 2007 to March 2009. The patients with HAP and VAP were followed prospectively until they expired or were discharged from the hospital. Results: One hundred and forty-six adult patients were included. Seventy percent of the patients were males with the mean age of 70.8 years. HAP was accounted for 24.7% and VAP 75.3%. Most of the patients (82.9%) had late-onset HAP or VAP with the median day of onset of pneumonia of 11 days. Two third of the patients were hospitalized in general medical wards. Bronchopneumonia was observed in 53.4% and multilobar pneumonia in 24.7%. A. baumanni was the most common isolated pathogen and 92.3% of them were multidrug-resistant (MDR) or pandrug-resistant (PDR). The other common isolated pathogens were K. pneumoniae, P. aeruginosa and methicillin-resistant S. aureus (MRSA). Carbapenem was the most commonly used initial antibiotic (45.9%) followed by colistin (21.9%) and cephalosporins (21.1%). The concordance of initial antibiotics was 58.9%. Antibiotics were modified 43.8% of the patients. Colistin was the most commonly used modified antibiotic followed by carbapenem. The modified antibiotics were concordant with isolated bacteria in 98.4%. The patients received mechanical ventilators in 81.5% with the median ventilator day of 10 days. At the initial response (72 hours after antibiotic therapy), an improvement was 56.8% and a mortality rate due to pneumonia was 14.4%. Death due to pneumonia at the end of treatment was 42.5%. The 30-day mortality from pneumonia was 45.9%. There were no significant differences in the outcomes of pneumonia between HAP and VAP. The factors associated with PDR-organisms were late-onset hospital-acquired pneumonia and previous carbapenem usage within 72 hours. Septic shock and bilateral lung involvement were significantly associated with unfavorable outcomes at 72 hours. Septic shock, severe sepsis, and previous carbapenem usage within 72 hours were significantly associated with mortality at the end of treatment and at 30 days after developing pneumonia. Conclusion: HAP and VAP remain to be very important hospital-acquired infections at Siriraj Hospital. The isolated pathogens are usually multidrug-resistant and the mortality rate remains high. The local data on prevalence of the isolated pathogens and their antibiotic susceptibility may help clinicians choose more appropriate initial antibiotics in order to improve the outcome and to decrease the emergence of resistant organisms.